Proponemos normas de uso adecuado de los recursos tecnológicos en los niños de segundo grado - Monzon Villena, Patricia Soledad (2021)
At present, educational systems around the world face the challenge of using Information and Communication Technologies to provide their students with the necessary tools and knowledge that are required in the 21st century. However, nowadays, as a result of the COVID 19 pandemic, the modality of face-to-face classes has been changed to distance classes and parents have been forced to acquire internet, a computer, tablet or a cell phone, but you have to Be cautious when browsing the internet, since, in many cases, the information displayed may lack veracity, as well as that, through the internet, different types of scam, deception, dependence on virtual games, accessing pages of people who can harm you such as pedophiles, human trafficking networks, pornography, etc. and as young children they are unaware of the dangers they can face. For all these reasons, in schools, teachers must make known rules for the proper use of ICTs seeking the common good and their consequences if we do not put them to good use. The sufficiency work has a structure that consists of three parts. In the first part, the introduction is located, which shows the problematic reality, justification and the objective of the study. In the second part, there is the theoretical support; here the definitions of technology, the area of Social Personnel, Competence and Capacity, the teaching process, pedagogical theories that support the use of ICT in learning, methodologies, means and materials, norms for an adequate Use of new technologies. In the third part, the pedagogical support is explained, here the work that was carried out in the learning sessions is detailed, taking into account the methodologies, resources and useful means to develop strategies, competencies and capacities of the Social Personnel area to achieve the objectives raised. Finally, the conclusions, the bibliography and the annexes.